Aktivitas Antioksidan Teh Kombucha dari Beberapa Varian Teh yang Berbeda - Azrini Khaerah; Fauzan Akbar (Seminar Nasional LP2M UNM, 2019)
Kombucha is kind of beverage fermented from tea by SCOBY (symbiotic Culture of Bacteria and Yeast). Many kond of leaves can used as substrate for making kombucha, such as tea leaves, coffe leaves, or else that contant high level of phenolic compound. The aim of this research are making four (4) kind of kombucha beverages and comparing these four (4) of antioxidant activity, total of acid and total of phenol. As the substrate, researcher using 4 kinds of tea, such as green tea (Sosro Heritage), black tea (Sosro Heritage), white tea (Twinnings) and oolong tea (Ti Guan Yin). All 4 kinds of tea fermented in to kombucha beverages. Then, analyzed for its antioxidant activity, total of acid and total of phenol. antioxidant activity analyzed by using DPPH method showed that the lower IC50 value, the higher antioxidant activity. Also showed that there is an increase of antioxidant activity of the samples between before and after fermented by SCOBY.as in thisi research, kombucha green tea has the highest antioxidant activity among all the samples. Fermentation also effects in the total of phenol compound, as the the total amont of phenol increase by the fermentation. Testing of total organic acid showed that the organic acid increase during the fernetation period.and, the acidity of teh mixture can effect the antioxidant activity, the more acid of the mixture, the lower of antioxidant activity. As the conlusion, fermentation by SCOBY can increase the antioxidant activity, also the organic acid content of kombucha tea.